Surau-Empowered Islamic Character Formation for Children: Darussalam's Model in Sumedang, Indonesia - Beni Ahmad Saebani; Taufiq Alamsyah (Jurnal Iman dan Spiritualitas, 2026)
Darussalam Islamic Boarding School in Sumedang Regency empowers local surau (prayer houses) to cultivate noble morals in children, preparing them for religious, national, and civic roles. Inappropriate guidance risks impeding comprehension and character formation; thus, drawing on Muhammad Utsman Khusyah's framework, efforts target personality development, monotheism, worship, muamalah, and Islamic culture, with surau as hubs for activity and internalization. Employing Participatory Action Research (PAR), the author co-designed and evaluated surau empowerment programs. Primary data derive from empowered surau teachers and child mentors. Findings reveal: (1) extensive surau development led by boarding school alumni trained as local educators; (2) multifaceted strategies, including Islamic Character Classes (honesty, discipline, responsibility, cooperation, politeness via lectures, discussions, games, modeling, simulations), integrated worship, moral fostering, social initiatives, and administrator training; and (3) enhanced surau functions yielding stronger Islamic character in children, revitalizing surau as centers for worship, ethics, and community engagement.